Iraqi primary care system in Kurdistan region: providers' perspectives on problems and opportunities for improvement - Shabila Nazar P; Al-Tawil Namir G; Al-Hadithi Tariq S; Sondorp Egbert; Vaughan Kelsey (BMC, 2012)
Abstract Background As part of a comprehensive study on the primary health care system in Iraq, we sought to explore primary care providers' perspectives about the main problems influencing the provision of primary care services and opportunities to improve the system. Methods A qualitative study based on four focus groups involving 40 primary care providers from 12 primary health care centres was conducted in Erbil governorate in the Iraqi Kurdistan region between July and October 2010. A topic guide was used to lead discussions and covered questions on positive aspects of and current problems with the primary care system in addition to the priority needs for its improvement. The discussions were fully transcribed and the qualitative data was analyzed by content analysis, followed by a thematic analysis. Results Problems facing the primary care system included inappropriate health service delivery (irrational use of health services, irrational treatment, poor referral system, poor infrastructure and poor hygiene), health workforce challenges (high number of specialists, uneven distribution of the health workforce, rapid turnover, lack of training and educational opportunities and discrepancies in the salary system), shortage in resources (shortage and low quality of medical supplies and shortage in financing), poor information technology and poor leadership/governance. The greatest emphasis was placed on poor organization of health services delivery, particularly the irrational use of health services and the related overcrowding and overload on primary care providers and health facilities. Suggestions for improving the system included application of a family medicine approach and ensuring effective planning and monitoring. Conclusions This study has provided a comprehensive understanding of the factors that negatively affect the primary care system in Iraq's Kurdistan region from the perspective of primary care providers. From their experience, primary care providers have a role in informing the community and policy makers about the main problems affecting this system, though improvements to the health care system must be taken up at the national level and involve other key stakeholders.